PUBLIC/PRIVATE DIMENSION AND ITS REFLECTION ON THE CROATIAN HIGHER EDUCATION SYSTEM WITH REGARD ON THE GLOBALISATION PROCESS (EU and comparative law issues and challenges series (ECLIC), 2020)
The system of higher education is, most frequently, perceived as a part of public service which is justified by the fact it is commonly analysed from that point of view. Since the same system has recently been subjected to privatisation and commercialisation processes, it is of outmost importance to define the notion of public and private within the context of higher education, which is the main aim of this paper. Furthermore, it is necessary to place the higher education system within the framework of public and/or private and provide a thorough analysis of the dimensions relevant for all the interested parties in the domain of public administration, that is, its segment significant for the topic. The first part of the paper is, therefore, primarily focused on presenting the dimensions public/private to the interested parties, while providing relevant arguments regarding the topic, so valid approach in this segment of public administration is found by combining various interpretations. Some of the questions particularly interesting to the author are being discussed in the central part of the paper: in what way is the division on public/private evident in the Croatian higher education system, is higher education perceived as public service and to what extent is its development affected by the globalisation process? In the final part of the paper, certain conclusions are made based on the facts presented in the paper, which could be used for improving efficacy and effectiveness of the higher education system in Croatia.